A novel process chain for the production of spherical sls polymer powders with good flowability - Schmidt, Jochen; Sachs, Marius; Blümel, Christina; Winzer, Bettina; Toni, Franziska; Wirth, Karl-Ernst; Peukert, Wolfgang (Proceedings of the 7th World Congress on Particle Technology, WCPT 2014, 2015)
Rapid prototyping has been applied so far in the production of special parts at low piece numbers. Currently, rapid prototyping gradually is transferred to additive manufacturing opening new applications. Especially selective laser sintering (SLS) applying polymer powder systems is promising. In the case of SLS basically only polyamide is available as an optimized powder material showing satisfying behavior during processing. Other types of polymer powders produced by cryogenic grinding show poor powder flowability as well as an unfavorable particle habitus resulting in poor device quality. In fact, it is challenging to produce laser sintering powders with small particle size, good flowability and processability. Within this account we present a novel process route for the production of spherical polymer micron-sized particles of good flowability. The feasibility of the process chain is demonstrated for polystyrene (PS) and poly butylene terephthalate (PBT) and the increase of powder flowability after the consecutive process steps has been monitored using a tensile strength tester. The influence of particle habitus and surface functionalization on powder flowability and its properties is discussed. In a first step polymer microparticles are produced by a wet grinding method at reduced temperatures. By this approach the mean particle size and the particle size distribution can be tuned between a few microns and several 10 microns and adapted to specific needs. The dependencies of mean product particle size, particle size distribution and grinding kinetics on stressing conditions, system composition and especially process temperature (increase of the brittleness of the polymer vs. increase of dampening of grinding bead motion with decreasing temperature) will be extensively discussed for the polymers PS, PBT, poly oxo methylene (POM) and Poly ether ether ketone (PEEK). The comminution products obtained typically consist of microparticles of irregular shape and poor powder flowability, i.e. these intermediate products are cohesive and thus will show poor SLS processability. An improvement of flowability of the ground polymer particles is achieved in a second step by changing their shape. The irregular particles are rounded using a heated downer reactor. It will be demonstrated that the 'degree' of rounding can be controlled by changing the temperature profile or the residence time. To further improve the flowability of the cohesive spherical polymer microparticles nanoparticles are adhered to the microparticles' surface in a third step. The improvement of powder flowability after the consecutive process steps is remarkable: rounded and dry-coated PS powders exhibit a strongly reduced tensile strength (by a factor 5) in comparison to the tensile strength of the edged PS comminution product. The improved flowability and packing behavior of the polymer powders open new options in SLS processing including the usage of much smaller polymer bead
Keywords: downer reactor; dry particle coating; polymers; selective laser sintering; wet grinding

A novel process route for the production of spherical LBM polymer powders with small size and good flowability - Schmidt, Jochen; Sachs, Marius; Blümel, Christina; Winzer, Bettina; Toni, Franziska; Wirth, Karl-Ernst; Peukert, Wolfgang (Powder Technology, 2014)
Rapid prototyping has been applied so far in the production of special parts at low piece numbers. Currently, 'rapid prototyping' gradually is transferred to additive manufacturing opening new applications. At present basically only polyamide (PA) is available as an optimized powder material showing satisfying behavior during processing in laser beam melting (LBM). Other types of polymer powders produced by cryogenic grinding show poor powder flowability as well as an unfavorable particle habitus resulting in poor device quality. In fact, it is challenging to produce laser sintering powders with small particle size, good flowability and processability. We present a novel process chain for the production of spherical polymer micron-sized particles of good flowability that can be applied to a large variety of polymers: in a first step polymer particles are produced by a wet grinding method that are rounded in a second step using a heated downer reactor. To increase the flowability of the cohesive spherical polymer particles further nanoparticles are adhered to the particle surface in the third step. We demonstrate an increase of powder flowability by a factor of 5. The influence of particle habitus and nanoparticle functionalization on powder flowability is discussed in detail. © 2014 Elsevier B.V.
Keywords: Downer reactor; Dry particle coating; Flowability; Laser beam melting (LBM); Polymers; Wet grinding

A novel process route for the production of spherical SLS polymer powders - Schmidt, Jochen; Sachs, Marius; Blümel, Christina; Winzer, Bettina; Toni, Franziska; Wirth, Karl-Ernst; Peukert, Wolfgang (Proceedings of PPS-30 : the 30th International Conference of the Polymer Processing Society : conference papers : 6-12 June 2014, Cleveland, Ohio, USA, 2015)
Currently, rapid prototyping gradually is transferred to additive manufacturing opening new applications. Especially selective laser sintering (SLS) is promising. One drawback is the limited choice of polymer materials available as optimized powders. Powders produced by cryogenic grinding show poor powder flowability resulting in poor device quality. Within this account we present a novel proceb route for the production of spherical polymer micron-sized particles of good flowability. The feasibility of the proceb chain is demonstrated for polystyrene e. In a first step polymer microparticles are produced by a wet grinding method. By this approach the mean particle size and the particle size distribution can be tuned between a few microns and several 10 microns. The applicability of this method will be discubed for different polymers and the dependencies of product particle size distribution on strebing conditions and proceb temperature will be outlined. The comminution products consist of microparticles of irregular shape and poor powder flowability. An improvement of flowability of the ground particles is achieved by changing their shape: they are rounded using a heated downer reactor. The influence of temperature profile and residence time on the product properties will be addrebed applying a viscous-flow sintering model. To further improve the flowability of the cohesive spherical polymer particles nanoparticles are adhered onto the microparticles' surface. The improvement of flowability is remarkable: rounded and dry-coated powders exhibit a strongly reduced tensile strength as compared to the comminution product. The improved polymer powders obtained by the proceb route proposed open new pobibilities in SLS procebing including the usage of much smaller polymer bead
Keywords: Downer reactor; Poly butylene terephthalate (PBT); Poly oxo methylene (POM); Polystyrene (PS); Rounding; Selective laser sintering (SLS); Wet grinding; rounding

Influence of carbon-coated iron nanoparticles on the Raman spectrum of liquid ethanol - Kiefer, Johannes; Toni, Franziska; Wirth, Karl-Ernst (Journal of Raman Spectroscopy, 2015)
Raman spectroscopy is applied to study the interactions between carbon‐coated iron nanoparticles and ethanol. The spectra reveal changes in the vibrational structure of ethanol, despite dispersion of only a very small amount of nanoparticles. The hydrogen bonding network of ethanol is significantly affected in the presence of the particles. This is revealed by frequency shifts throughout the spectrum as well as the modification of the OH stretching band of the alcohol. The carbon shell of the nanoparticles does not exhibit polar groups, and hence the non‐polar interactions in the system are strengthened and the hydrogen bonding is weakene
Keywords: elastic scattering; composite; Raman scattering; molecular interactions

Production of well dispersible single walled carbon nanotubes via a "floating catalyst"-method - Toni, Franziska; Xing, Haichen; Walter, Johannes; Strauß, Volker; Nacken, Thomas; Damm, Cornelia; Wirth, Karl-Ernst; Guldi, Dirk Michael; Peukert, Wolfgang (Chemical Engineering Science, 2015)
In this paper, we present a unique process chain for the production of single-walled carbon nanotubes (SWCNT) and document the relationship between the process parameters in gas phase production, the dispersibility of SWCNTs in aqueous solutions of sodium cholate and their properties. SWCNTs were prepared by a "floating catalyst" method using a solution of ferrocene in ethanol as precursor. Production rates in the range from 5 to 20. mg/h were achieved by using an optimized riser reactor design, which enables reduction of undesired wall-sticking of the catalyst particles and SWCNTs. Products featuring iron catalyst contents less than 30. wt% were obtained for low precursor concentrations in combination with short residence time in the reactor. Transmission electron microscopy (TEM) and statistical Raman analyses of the products reveal that the SWCNTs exhibit a diameter distribution ranging from 0.5 to 2.0. nm. Processing conditions, including precursor concentration, residence time, etc. were found to have only a slight impact on the mean geometric SWCNT diameter. Sonication based post-processing of the as-prepared SWCNTs in aqueous solutions of sodium cholate leads to an effective individualization of SWCNTs as proven by atomic force microscopy (AFM), 3D fluorescence spectroscopy, and by multi-wavelength analytical ultracentrifugation (AUC). Overall, the dispersibility of the non-purified SWCNTs in a 2. wt% aqueous solution of sodium cholate increases as the ferrocene partial pressure is decreased and, in turn, the catalyst concentration is reduced in the gas phase. Statistical Raman spectroscopy performed with the SWCNTs reveals that more than 75% of the produced carbon species are SWCNTs and that about 2/3 are semiconducting.
Keywords: Analytical ultracentrifugation and Raman spectroscopy; CNTs; Dispersion; Floating catalyst

Rounding of irregular polymer particles in a downer reactor - Sachs, Marius; Schmidt, Jochen; Toni, Franziska; Blümel, Christina; Winzer, Bettina; Peukert, Wolfgang; Wirth, Karl-Ernst (Procedia Engineering 102, 2015)
In the past additive manufacturing processes relying on beam-based methods such as selective laser sintering (SLS) of polymers were almost exclusively applied for the generation of prototypes. In recent years, however, these methods are increasingly applied in the serial production of e.g. special parts to be used in the automotive industry. With this increased relevance in industrial applications, the demands on the powder material increased as well [1]. The so far used polymer materials show weak performance regarding the mechanical stability of processed parts. In consequence, there is a need for fine powders of different polymers showing good powder flowability and high bulk density. Currently, the commercial availability of polymer powders for SLS is very limited and the production processes are still not reliable enough due to poor powder characteristics. Within this contribution a process for the production of spherical polymer micro particles showing good powder flowability is presented [2]. It has been recently shown [3] for different materials that commercially available polymer granules can be ground down to the micron size range by a wet grinding process. Due to the grinding process the produced micron-sized particles are in a chiseled state, which leads to a bad flowability of the powder material. To overcome this problem the single particles are melted in a heated downer reactor and spherical particles are obtained by using the effect of the surface tension [3]. The rounding of ground PS microparticles was performed in a downer reactor with a length of 1,600 mm and a diameter of 25 mm. The reactor temperature was set 100 °C above the melting temperature of the treated material. The laminar flow regime in the downer reactor allows a well-defined residence time of particles and the surrounding gas [4]. The design of the downer reactor allows transferring the polymer particles in the molten state whilst avoiding contact between the single particles and between molten particles and the reactor wall. The mechanism of the rounding process in dependence of particle size, interfacial tension and melt viscosity will be shown within a sintering model [6]. The influence of residence time and overall solids density in the downer reactor on the particle shape and on the flowability of the bulk material is shown. Estimates from the sintering model allow for a reliable reactor design.<br
Keywords: additive manufacturing; particle rounding; downer reactor; polymers